KEMAMPUAN BERPIKIR KRITIS MATERI SEL MELALUI PRAKTIKUM BERBASIS INVITATION INTO INQUIRY - Megantara, Afifa; Sukaesih, Sri; Mubarok, Ibnul (Journal of Biology Education, 2013)
Invitation into inquiry-based lab work is necessary to study its effectiveness on students critical thinking skills because similar studies have not been done primarily on the cell material. Learning begins by giving a problem to students who are prepared in the form of another question asked students to design practice. This study aims to determine the effectiveness of practice-based inquiry into invitation to high school students critical thinking skills N 1 Dukun on the cell material. This study was Quasi Experimental with Control Group Design Nonequivalent design is applied to the class XI IPA 2 as the experimental class and class XI IPA 3 as controls. Sampling was purposive sample was determined by the technique. N-gain test results show that the average N-gain critical thinking skills of students in the experimental class higher than the control class. In the experimental class average N-gain 0.46, while the control class is 0.32. The results of the t-test showed that the value of P = 0.485 for 2-tailed test, so it can be said that there is a difference in students critical thinking skills class experiments with the control class. Conclusions from this research is practice-based inquiry into the invitation-effective in improving students critical thinking skills. Praktikum berbasis invitation into inquiry perlu diteliti efektivitasnya terhadap kemampuan berpikir kritis siswa karena belum pernah dilakukan penelitian sejenis terutama pada materi sel. Pembelajaran dimulai dengan memberikan suatu permasalahan kepada siswa yang disusun dalam bentuk pertanyaan selanjutnya siswa diajak untuk merancang praktikum. Penelitian ini bertujuan untuk mengetahui efektivitas praktikum berbasis invitation into inquiry terhadap kemampuan berpikir kritis siswa SMA N 1 Dukun pada materi sel. Penelitian ini merupakan penelitian Quasi Eksperimental dengan desain Nonequivalent Control Group Design yang diterapkan pada kelas XI IPA 2 sebagai kelas eksperimen dan XI IPA 3 sebagai kelas kontrol. Pengambilan sampel ditentukan dengan teknik purposive sample. Hasil uji N-gain menunjukkan bahwa rata-rata N-gain kemampuan berpikir kritis siswa pada kelas eksperimen lebih tinggi dari pada kelas kontrol. Pada kelas ekperimen rata-rata N-gain 0,46 sedangkan pada kelas kontrol 0,32. Hasil uji-t menunjukkan bahwa nilai P = 0,485 untuk uji 2-sisi, sehingga dapat dikatakan bahwa ada perbedaan kemampuan berpikir kritis siswa kelas eksperimen dengan kelas kontrol. Simpulan dari penelitian ini adalah praktikum berbasis invitation into inquiry efektif dalam meningkatkan kemampuan berpikir kritis siswa.